2016
DOI: 10.21767/2473-6457.100002
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Protoporphyrin IX induced Photodynamic Therapy with a Topical Iron Chelating Agent in a Normal Skin Model

Abstract: Protoporphyrin IX (PpIX)-induced photodynamic therapy (PDT) is being utilised within dermatological practice as a topical method of localised ablation of nonmelanoma skin cancer/precancer. Standardised protocols have been implemented to good effect when the disease remains superficial but improvement is required to widen the application of this light activated drug therapy to treat thicker or acrally located conditions. As innate haem biosynthesis is exploited to accumulate the light sensitive PpIX from a topi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…We have previously demonstrated that CP94 significantly increases the efficacy of MAL-based photodynamic cell killing in a range of human cultured cell types, more effectively than the more established iron chelator desferrioxamine [41] , [42] and is effective with all PpIX congeners (ALA, MAL and HAL (hexaminolevulinate)) and oxygen concentrations (5%, 20% and 40%) investigated to date [43] . Furthermore these experimental findings have translated into greater reductions in tumour thickness when applied to skin cancers clinically [30] , [31] as CP94 is effective as a topical formulation [44] . Here, we have shown that, following treatment with 0.5 mM MAL and irradiation (25 J/cm 2 ), A431 cells died primarily by necrosis at each time point measured, with little more than “background” apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that CP94 significantly increases the efficacy of MAL-based photodynamic cell killing in a range of human cultured cell types, more effectively than the more established iron chelator desferrioxamine [41] , [42] and is effective with all PpIX congeners (ALA, MAL and HAL (hexaminolevulinate)) and oxygen concentrations (5%, 20% and 40%) investigated to date [43] . Furthermore these experimental findings have translated into greater reductions in tumour thickness when applied to skin cancers clinically [30] , [31] as CP94 is effective as a topical formulation [44] . Here, we have shown that, following treatment with 0.5 mM MAL and irradiation (25 J/cm 2 ), A431 cells died primarily by necrosis at each time point measured, with little more than “background” apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…It is closely related to the clinically established oral iron chelating agent Deferiprone (1,2‐dimethyl‐3‐hydroxypyridin‐4‐one hydrochloride (CP20); Ferriprox, Swedish Orphan Biovitrum Ltd, Sweden) but CP94 was found to be superior to CP20 for this particular application (PpIX‐PDT enhancement) in previous animal studies . CP94 is particularly effective at chelating intracellular iron and has a lower molecular weight and higher lipophilicity than either DFO or EDTA and is well suited to augmenting dermatological PDT as it can be applied topically . CP94 has already been demonstrated to enhance ALA‐induced PpIX fluorescence and to also produce greater tumor necrosis within animal models .…”
Section: Introductionmentioning
confidence: 99%
“…PpIX accumulation and caused a better clearance rate as presented in Table2 [71]. DFO was also used, but Curnow et al Have recently reported that CP94 was a more efficient enhancer of PpIX-induced PDT in vitro than DFO [1].…”
Section: Agents That Control Heme Cycle and Promote Ppix Accumulationmentioning
confidence: 99%
“…Protoporphyrin IX-induced PDT has been widely used in dermatological practice such as treatment of skin cancers [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation